Penggunaan Pribahasa (Sanepa) Jawa dalam Kebudayaan Masyarakat di Surakarta - Riris Tiani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
The Indonesian nation has a wealth of oral traditions or extraordinary cultural traditions, which are spread across ethnic groups in Indonesia as a cultural heritage of the past. The wealth of oral traditions or cultural traditions becomes a source of wealth of local wisdom. This local wisdom must be used to build the character and identity of human resources and build this nation. Sanepan Java is still commonly found in the daily lives of the people of Central Java. Javanese language as part of idiomatic language Javanese is not only a verbal language that discusses beauty, but it is a language that is owned by Javanese for the benefit of Javanese people. This research questions the symbolic meaning and the application of sanepan in the life of Javanese people. The results of this study about the future of Java contain the meaning of discussion, mutual cooperation, harmony, care and advice. Sanepan Java contains local wisdom that is still relevant to be applied to the current conditions because it contains noble values of life. Most of it means conflict of meaning because it is interpreted by lexical. The noble values embodied in the future of Java become local wisdom and Javanese culture that needs to be preserved. Sanepan Java is a proof of the existence of the strength of the noble spirit of the Javanese people who have merged with nature.